Heterogeneous subpopulations of adventitial progenitor cells regulate vascular homeostasis and pathological vascular remodelling. Issue 6 (14th May 2021) - Jolly, Austin J; Lu, Sizhao; Strand, Keith A; Dubner, Allison M; Mutryn, Marie F; Nemenoff, Raphael A; Majesky, Mark W; Moulton, Karen S; Weiser-Evans, Mary C M
Abstract: Cardiovascular diseases are characterized by chronic vascular dysfunction and provoke pathological remodelling events, such as neointima formation, atherosclerotic lesion development, and adventitial fibrosis. While lineage-tracing studies have shown that phenotypically modulated smooth muscle cells (SMCs) are the major cellular component of neointimal lesions, the cellular origins and microenvironmental signalling mechanisms that underlie remodelling along the adventitial vascular layer are not fully understood. However, a growing body of evidence supports a unique population of adventitial lineage-restricted progenitor cells expressing the stem cell marker, stem cell antigen-1 (Sca1; AdvSca1 cells) as important effectors of adventitial remodelling and suggests that they are at least partially responsible for subsequent pathological changes that occur in the media and intima. AdvSca1 cells are being studied in murine models of atherosclerosis, perivascular fibrosis, and neointima formation in response to acute vascular injury. Depending on the experimental conditions, AdvSca1 cells exhibit the capacity to differentiate into SMCs, endothelial cells, chondrocytes, adipocytes, and pro-remodelling cells, such as myofibroblasts and macrophages. These data indicate that AdvSca1 cells may be a targetable cell population to influence the outcomes of pathologic vascular remodelling. Important questions remain regarding the origins of AdvSca1 cells and the essential signalling mechanisms and microenvironmental factors that regulate both maintenance of their stem-like, progenitor phenotype and their differentiation into lineage-specified cell types. Adding complexity to the story, recent data indicate that the collective population of adventitial progenitor cells is likely composed of several smaller, lineage-restricted subpopulations, which are not fully defined by their transcriptomic profile and differentiation capabilities. The aim of this review is to outline the heterogeneity of Sca1+ adventitial progenitor cells, summarize their role in vascular homeostasis and remodelling, and comment on their translational relevance in humans. Graphical Abstract: